Isolation and Antimicrobial Resistance Mapping of Escherichia coli Isolates from Various Animal Species and Birds - Khant, Ravindra B; Pathan, Fatimazohra A; Mathakiya, Rafiyuddin A; Rana, Niyati M; Nimavat, Vipul R; Vahora , Aatika S (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
In the present study, 257 faecal samples were collected from diarrheic and healthy cattle, buffaloes, dogs, and poultry in and around Anand, Gujarat. Based on cultural and biochemical characterization, 200 isolates (77.82%) were identified as Escherichia coli. Antibiotic susceptibility testing using 22 antimicrobials revealed high resistance to cephalothin (up to 100%), followed by pefloxacin (84%), erythromycin (72%), and cefoperazone (64%), while complete sensitivity was observed toward amoxyclav, colistin, and amikacin. Extended-spectrum β-lactamase (ESBL) production was phenotypically confirmed in 52.00% of isolates from diseased poultry, followed by 44.00% from diarrheic cattle, 40.0% from healthy cattle and diarrheic buffaloes, each and 20.00% from healthy dogs. PCR based screening of 200 isolates for 14 different antibiotic resistance genes (ARGs) detected multiple ARGs, with tetA (47.50%), followed by tetB (41.50%), sulI (39.00%), aadA1 (32.50%) and qnrS (29.50), while β-lactamase genes (blaTEM, blaOXA, blaSHV) and integron gene intl1 were detected in 10.50-27.00% of the isolates. The findings highlight widespread dissemination of multidrug-resistant and ESBL-producing E. coli among livestock and poultry, emphasizing the need for judicious antibiotic use and regular AMR surveillance in animal populations.